Characterization of Regulatory T-Cell Markers in CD4+ T Cells of the Upper Airway Mucosa - Ballke, Christina (PLoS One, 2016)
CD4+ T regulatory cells (Tregs) comprise a heterogeneous population of cells the regulate immune responses and prevent autoimmunity. Most reports on human Tregs are derived from studies of peripheral blood, although Tregs mainly exert their functions in the periphery. Here we performed a detailed analysis of Tregs in the human upper airway mucosa under non-inflammatory conditions, and found that 10% of all CD4+ T cells expressed the transcription factor FOXP3 and the memory marker CD45RO, as well as high levels of CTLA-4. The majority of FOXP3+CD4+ T cells co-expressed the transcription factor Helios and produced very little cytokines, compatible with being thymus-derived Tregs. FOXP3+Helios-CD4+ T cells were more heterogeneous. A mean of 24% produced the immunomodulatory cytokine IL-10, whereas a large fraction also produced IL-2, IFN-μ or IL-17. A significant population (6%) of FOXP3-negative T cells also produced IL-10, usually in combination with IFN-μ. Together, we found that CD4+ T cells in the upper airways differed functionally from their counterparts in peripheral blood, including higher expression of IL-10. Moreover, our findings suggest that several subsets of CD4+ T cells with functionally distinct regulatory properties reside in the upper airway mucosa which should be taken into account when targeting Tregs for therapy.